Alcuino de York y su epistolario - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 2001)
This paper deals with Alcuin of York's thinking and personality reflected in his letters. It is an analysis of the different types of Alcuin's epistles: doctrinal, friendship, officials (according to his roles as an abbot, a royal court functionary and an educator), and other author's letters. It is possible to discover in these letters many aspects of the political, ecclesiastical and theological matters in the Charlemagne's age as well as a human and personal face of Alcuin of York.
Fil: Peretó Rivas, Rubén A. Universidad de Buenos Aires; Argentina.
Keywords: FILOSOFÍA MEDIEVAL; CORRESPONDENCIA; CARTAS; DOCUMENTO; TEOLOGÍA; RENACIMIENTO; EDAD MEDIA; PODER ECLESIÁSTICO; ALCUINO DE YORKALCUINO DE YORK